Intracoronary nitroglycerin injection through a homemade side-hole ballon for coronary slow/no-reflow phenomenon prevention. (25th November 2020) - Gu, C; Qiao, R.U.I
Abstract: Objective: The evaluate nitroglycerin-injection during the homemade side-hole ballon into the proximal segment of the target lesion by TIMI blood flow and the corrected TIMI frame count (CTFC) during primary PCI for patients with ST-segment elevation myocardial infarction (STEMI). Methods: All patients were diagnosed with STEMI. A dual antiplatelet therapy was given; patients were able to receive pPCI. The basic TIMI blood flow and CTFC were recorded after angiography and randomized according to the random number table by group A (n=61, early nitroglycerin injection via side-hole ballon) andgroup B (n=59, Traditional protocol PCI). Side-hole ballon was made by the ballon that passed the target lesion and puncture it with holes with needle. The TIMI blood flow and CTFC status immediately after the pPCI and the related events during the hospitalization and 6 months discharged. Results: There were no significant differences between the baseline and laboratory parameters of the two groups (P>0.05). Also no differences in TIMI blood flow and CTFC frame before the target vessel was opened (P>0.05), Further no difference in number of implanted stents, stent length and diameter. The immediate effect after pPCI showed, the early nitroglycerin injection via side-hole ballon have effect on the TIMI blood flow (P=0.027), the CTFC (P=0.007) and the proportion of slow/no-reflow (6.56% vs. 22.03%, P=0.015). There was no difference in the incidence of MACE between two groups during hospitalization and 30 days follow-up. The incidence of MACE at 6 months follow-up was significantly lower in group A (1.63% vs. 10.17%, P=0.046). Conclusion: In pPCI process, the early upstream nitroglycerin injection via homemade side-hole ballon can significantly reduce the incidence of slow/no-reflow after pPCI while the guidewire/balloon passes through the lesion. After pretreatment by this manner, the patient's 6-month MACE rate can be significantly improved. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): The basic research project of Anhui Medical University